EVALUASI SIFAT ANTIBAKTERI DAN BIOAKTIVITAS TI6AL4V DENGAN PELAPIS ASAM TANAT, SERISIN, DAN GRAPHENE OXIDE MENGGUNAKAN METODE LAYER-BY-LAYER - R.M. Simanjuntak, Yohana
Titanium alloy, Ti6Al4V, is the most used material for bone implants, yet it is still prone to implantation failure. This issue is caused by bacterial infection due to high implant-bacteria interfacial interactions and a lack of osseointegration because of low implant-bone interfacial interactions. This study focuses on modifying the surface of Ti6Al4V using coatings to enhance its antibacterial properties and bioactivity. Tannic acid (TA), sericin (SS), and graphene oxide (GO) were deposited using the layer-by-layer method on the Ti6Al4V surface to produce a TA-SS-GO layer. Tannic acid acts as a coupling agent between Ti6Al4V and the sericin layer, sericin plays a role in enhancing bioactivity, and GO acts as an antibacterial agent. SEM-EDS characterization, XPS, and water contact angle testing confirmed the successful deposition of each coating material. Antibacterial testing against Staphylococcus aureus bacteria showed that the TA-SS-GO layer has the highest bacterial reduction capability, which is 91%. An evaluation of the stability of antibacterial properties over 14 days in SBF (Simulated Body Fluid) showed that the TA-SS layer is stable, while the TA and TA-SS-GO layers experienced a performance decline of 13% and 2%, respectively. Cell viability evaluation on 3T3 mouse fibroblast cells showed that TA-SS and TA-SS-GO are non-toxic. Hydroxyapatite (HAP) formation evaluation over 14 days in SBF showed that the TA-SS layer has the best bioactivity, while the addition of a GO layer on top of it hindered the performance of sericin. Overall, the results of the study indicate that the TA-SS coating has the best potential for improving the antibacterial properties and bioactivity of Ti6Al4V implants.